A psychological perspective on Elitism : influence of perceived threat and similarity on Elitist attitudes through mediation pathways - Cheah, Dave Koon Sum (Nanyang Technological University, 2020)
Elitism is a concept ingrained in the collective consciousness of Singapore society. Even though Elitism has been viewed as an undesirable attitude, little research could be found on how Elitist attitudes could be changed, or how they could be related to other psychological constructs. This study therefore aims to examine how Elitism has been defined in Singapore, and whether it could be changed through the influence of perceived threat or perceived similarity from an outgroup lower in social standing compared to participants. The possibility of two psychological mediators, social dominance orientation (SDO) and psychological entitlement, affecting the relationship of Elitism with these outgroup perceptions were also explored. 201 university undergraduate students participated and underwent one of three experimental conditions meant to influence their perceived similarity or threat from the relevant outgroup, following which the attitudes of interest were measured through an online self-report questionnaire. Literature review and factor analyses of empirical data found that key definitional components of Elitism include deference to Elite individuals or groups, along with negative perceptions towards those perceived to have poorer capabilities and social standing. The study found that perceived threat did not influence Elitist attitudes among participants, while perceived similarity helped to diminish Elitism as hypothesized. The mediation relationships of SDO and psychological entitlement on perceived similarity and Elitism were also found to be significant through a structural equation modelling (SEM) analysis. The implications for practical management of Elitism and future research were discussed.